2016
DOI: 10.1073/pnas.1602306113
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Fluidigm C1 platform for RNA sequencing of single mouse pancreatic islet cells

Abstract: This study provides an assessment of the Fluidigm C1 platform for RNA sequencing of single mouse pancreatic islet cells. The system combines microfluidic technology and nanoliter-scale reactions. We sequenced 622 cells, allowing identification of 341 islet cells with high-quality gene expression profiles. The cells clustered into populations of α-cells (5%), β-cells (92%), δ-cells (1%), and pancreatic polypeptide cells (2%). We identified cell-type-specific transcription factors and pathways primarily involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
129
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(145 citation statements)
references
References 23 publications
(22 reference statements)
13
129
0
Order By: Relevance
“…S1). The expression of ATF5 in β cells of the murine pancreatic islet is consistent with several single-cell transcriptomic studies that identified Atf5 transcript in murine and human β cells (27)(28)(29).…”
Section: Resultssupporting
confidence: 87%
“…S1). The expression of ATF5 in β cells of the murine pancreatic islet is consistent with several single-cell transcriptomic studies that identified Atf5 transcript in murine and human β cells (27)(28)(29).…”
Section: Resultssupporting
confidence: 87%
“…1C). Cells expressing less than 3500 genes (n = 72) also exhibited high mitochondrial alignment rates and other reported transcriptional metrics of cell death and/or poor quality (Ilicic et al 2016;Xin et al 2016) and were removed from subsequent analyses (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Single cells were captured and processed on a Fluidigm C1 instrument in collaboration with Regeneron Pharmaceuticals as described in ref. 45. For analysis of cells isolated from grafted arches from CD68-GFP reporter mice, samples were processed as described above, and flow cytometry was conducted on a BD LSRII UV.…”
Section: Methodsmentioning
confidence: 99%